Upaya Memaksimalkan Kewang Laut Dalam Pelaksanaan Sasi Laut - Novyta Uktolseja; Rory Jeff Akyuwen; Agustina Balik (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Efforts to Maximize Kewang Laut in the Implementation of Sasi Laut and as an Effort to Improve Professionalism of Kewang Laut and Sasi Laut, are one of the factors where the community's dependence in this case is related to the protection of kewang in supervising and maintaining marine biota in the marine area of the indigenous peoples.Purposes of Devotion: The purpose of this service is to provide understanding to the community regarding Sasi Laut and Kewang Laut, To strengthen public understanding regarding efforts to maximize kewang Laut in the implementation of Sasi Laut, To socialize and provide understanding to the community about the efforts that can be done in preventing violations of the sea. marine law violation. Method of Devotion: In accordance with the problems and objectives of this service, the type of research used is empirical research, namely a legal research method that uses empirical facts taken from human behavior, both verbal behavior obtained from interviews and real behavior carried out through direct observation. The Problem Approach used is the Conceptual Approach, which is an approach in legal research that provides an analytical point of view of problem solving in legal research seen from the aspects of the legal concepts that lie behind it, or even can be seen from the values contained in the norm.Results of the Devotion: To create a customary law community that is good at utilizing its marine power, the role of kewang sea is needed in the implementation of sea sasi, so the right efforts to overcome the obstacles that hinder the process of optimizing kewang sea are: 1). increase a sense of love for Nature both sea and land. 2). Improving and Empowering Kewang Laut as a marine human resource. 3). Improving and Strengthening the role of kewang Laut. 4). Strengthening Security through Kewang Laut. Thus, the effort to maintain the role of the kewang Laut in its role and function is to be able to maintain and oversee marine biota or natural resources in the country which are the needs of indigenous peoples. For this reason, the customary institution which is the customary government must always be able to oversee every decision issued by the customary stakeholders.